Experience, Aptitude, and Individual Differences in Linguistic Attainment: A Comparison of Native and Nonnative Speakers. (22nd October 2018) - Dąbrowska, Ewa
Abstract: This study compares the performance of native speakers and adult second language (L2) learners on tasks tapping proficiency in grammar, vocabulary, and collocations. In addition, data were collected on several predictors of individual differences in linguistic attainment, including some related to language experience (print exposure, education, and—for L2 speakers—length of residence and use of English) and some relating to an individual's aptitude to learn (language analytic ability and nonverbal intelligence) as well as age and (for L2 speakers) age of arrival. As anticipated, the native group outperformed L2 speakers on all three language measures, although the effect sizes were much larger for collocations than for grammar or vocabulary. Crucially, there were vast individual differences in both groups and considerable overlap between groups, particularly for grammar. Regression analyses revealed both similarities and differences between native and nonnative speakers in which nonlinguistic measures best predict performance on the language tasks.